2011
DOI: 10.1007/s00704-011-0545-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating daily global solar radiation during the growing season in Northeast China using the Ångström–Prescott model

Abstract: Daily global solar radiation is an important input required in most crop models. In the present study, a sunshine-based model, the Ångström-Prescott model, is employed to estimate daily global solar radiation on a horizontal surface during the growing season in Northeast China. Data from six control groups are used. The controls include the entire sequence, precipitation days, and non-precipitation days both during the growing season and year-round. Estimations are validated by comparing the calculated values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
14
0
5
Order By: Relevance
“…Our research results revealed that, on the whole, the solar radiation over NEC had an obviously upward trend during the study period of 1980-2010, which was consistent with results of previous studies [44][45][46]. This estimated increasing trend was also in accordance with the findings of Wild et al (2005), who deemed that the surface of the Earth has shifted from "dark" to "bright" over the past decade.…”
Section: Dynamic Intensity Of Solar Radiationsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research results revealed that, on the whole, the solar radiation over NEC had an obviously upward trend during the study period of 1980-2010, which was consistent with results of previous studies [44][45][46]. This estimated increasing trend was also in accordance with the findings of Wild et al (2005), who deemed that the surface of the Earth has shifted from "dark" to "bright" over the past decade.…”
Section: Dynamic Intensity Of Solar Radiationsupporting
confidence: 91%
“…Solar radiation is necessary for the growth of vegetation; therefore, it is critical to quantitatively analyze its spatiotemporal variation to implement proper and reasonable vegetation restoration plans and agricultural ecological patterns. However, the majority of previous studies regarding estimating solar radiation over NEC adopted climate empirical models and solar radiative models, and dynamic changes in solar radiation of this region were limited to traditional trend analyses that did not reflect the continuous, dynamic changes [44][45][46]. Therefore, the main objectives of this study were to (1) estimate solar radiation over NEC using the ACO-BPNN model and (2) apply the intensity analysis method to characterize the dynamic variations in solar radiation of this region.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the availability of precise solar radiation data is a fundamental requirement for solar system specialists to successfully simulate, operate, and monitor the solar energy technologies for a variety of applications (Bannani et al 2006;Benghanem and Mellit 2014;Flores et al 2015). Unfortunately, the reliable measured solar radiation data, even in the form of global solar radiation, are not accessible in many sites due to a series of obstacles including the required costs for purchasing, maintaining, and calibrating the measurement equipment (Wu et al 2012;Shamim et al 2015). Thus, this has necessitated the development of proper models for accurate prediction of global solar radiation using a considerable number of input elements (Gueymard 2014;Yadav and Chandel 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Also, the number of global policies and targets to support the development of solar energy technologies has been increasing rapidly. Nevertheless, despite such great advances in solar energy applications, the unavailability of measured solar radiation data, due to high costs required to purchase and calibrate the instruments, is still a huge barrier to develop the solar energy systems properly and efficiently in many parts of the globe (Mubiru et al 2007;Wu et al 2012;Shamim et al 2015). As a consequence, collecting and processing precise solar radiation data, especially in the form of horizontal global solar radiation, are of vital importance.…”
Section: Introductionmentioning
confidence: 99%